(untitled) (Research, Society and Development, 2022)
The Lavandula dentata L. (Lamiaceae) is used by Mediterranean peoples for its numerous applications. Its secondary pathways operate producing a wide variety of volatile terpenoids that act as efficient antifungals and bactericides. Therefore, this research aimed to evaluate the antimicrobial potential of the organic hydrolate and organic essential oil of L. dentata against bacterial strains of Escherichia coli (ATCC 8739), Staphylococcus aureus (ATCC 6538 and ATCC 25923), Streptococcus pyogenes (ATCC 19615) and Mycobacterium tuberculosis (ATCC 25177), yeast strains of Candida albicans (ATCC 10231), Candida parapsilosis (ATCC 22019), Cryptococcus neoformans var. grubii. (ATCC 90113) and the filamentous fungus Fusarium oxysporum f. sp. cubense (CMAA 1807) by disk diffusion method. The disk diffusion test was performed in Mueller Hinton Agar medium, with 2% glucose supplementation for the yeasts. As a positive control, 70% ethyl alcohol was adopted, the antibiotic cephalexin (5 ug) and the antifungal fluconazole (25 ug) were chosen to evaluate the sensitivity profile. The statistical test of variance ANOVA was adopted to determine the significance of the results obtained. The essential oil was efficient against the microorganisms evaluated, especially against the gram-positive strains of Staphylococcus aureus and Mycobacterium tuberculosis. It also showed a higher inhibitory potential to ethyl alcohol against Candida albicans and Streptococcus pyogenes. Therefore, it is inferred that the essential oil of Lavandula dentata has high antimicrobial capacity against gram-positive strains, presenting itself as a potential antimicrobial agent against microbial strains of considerable importance.